2014
DOI: 10.2527/jas.2013-6923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial phytase on phytate P degradation and apparent digestibility of total P and Ca throughout the gastrointestinal tract of the growing pig1

Abstract: The effect of a dietary microbial phytase on mineral digestibility throughout the gastrointestinal tract (GIT) of the growing pig was studied. Thirty-two entire male pigs (~22 kg BW) were allocated equally to 4 corn-soybean meal diets. One diet was adequate in total P and Ca, the second diet was deficient in total P and Ca (low-P diet), and the third and fourth diets were the low-P diet with microbial phytase added at 1,107 U/kg or 2,215 U/kg, respectively. Titanium dioxide (3 g/kg) was included in the diets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
9
19
0
Order By: Relevance
“…By contrast, the improvement in Ca availability found in this study is in accordance with the results found in many studies (BRAÑA et al, 2006;GUGGENBUHL et al, 2007;KIES et al, 2006;KIM et al, 2005KIM et al, , 2008POULSEN et al, 2010a;KAY, 2007;ALMEIDA et al, 2013;MADRID et al, 2013;FÁVERO et al, 2014;RUTHERFURD et al, 2014;KAHINDI et al, 2015), which show that phytase can effectively improve not only P availability but also Ca availability.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…By contrast, the improvement in Ca availability found in this study is in accordance with the results found in many studies (BRAÑA et al, 2006;GUGGENBUHL et al, 2007;KIES et al, 2006;KIM et al, 2005KIM et al, , 2008POULSEN et al, 2010a;KAY, 2007;ALMEIDA et al, 2013;MADRID et al, 2013;FÁVERO et al, 2014;RUTHERFURD et al, 2014;KAHINDI et al, 2015), which show that phytase can effectively improve not only P availability but also Ca availability.…”
Section: Resultssupporting
confidence: 93%
“…In addition, part of the Ca complexed by the phytate molecule was liberated and available for the animals. These results confirms the efficacy of phytase in improving P and Ca availabilities and are in accordance with the findings of several researchers (KIM et al, 2005;BRAÑA et al, 2006;KIES et al, 2006;NYACHOTI et al, 2006;GUGGENBUHL et al, 2007;HTOO et al, 2007;POULSEN et al, 2007;MOEHN et al, 2007;KAY, 2007;KIM et al, 2008;POMAR et al, 2008;HILL et al, 2009;POULSEN et al, 2010aPOULSEN et al, , 2010bATAKORA et al, 2011;ALMEIDA et al, 2013;MADRID et al, 2013;FÁVERO et al, 2014;RUTHERFURD et al, 2014;KAHINDI et al, 2015) who verified improvements of P availability from 4.1% to greater than 100% with phytase addition in pig diets. This great range in P availability improvement is a consequence of differences in the design of the mentioned studies, such as the use of different feed ingredients, different phytase levels or activities, use of other enzymes in combination with phytase and diets with different nutrient levels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the low availability of P in cereals for monogastric livestock species, a range of feed processing techniques has been applied to reduce their InsP 6 concentration. Yet, in the feeding of monogastric livestock species such as swine and poultry, processing techniques used to increase P availability of feeds are often restricted to microbial phytase supplementation [8], [32]. Our data indicated that treatment of barley grain with LA and LA-H was able to decrease the InsP 6 concentration and thus potentially increase P availability in barley.…”
Section: Discussionmentioning
confidence: 77%
“…estimated that in growing/finishing pigs fed a corn–SBM‐based diet supplementation of 900 FTU A. niger phytase degraded about 38% phytate. Rutherfurd et al . reported that addition of 1000 and 2000 FTU kg −1 of a Citrobacter braakii phytase to a pig diet resulted in increased ileal phytate degradation by 29 and 32 percentage points, respectively, compared to a negative control.…”
Section: Phytase Efficacy Assessmentmentioning
confidence: 99%